Contribuições do Programa Residência Pedagógica (PRP) na formação inicial de professores no munícipio de Bragança-PA - PENHA, Márcia Janaína Costa (2023)
The Pedagogical Residency Program (PRP) plays an important role in the initial training of teachers, as it provides diverse experiences, knowledge exchange, the exercise of teaching practice, and contact with the school scenario. Thus, this work has as main objective to analyze the formative contributions of the Pedagogical Residency Program (PRP) provided in the initial formation of the residents of the Degree in Natural Sciences and Biological Sciences of the IECOS/UFPA, Campus Bragança-PA. The present research is characterized as qualitative, of a descriptive-analytical nature, which takes a semi-structured questionnaire and the final reports of the resident professors for data construction. For data analysis we used the Content Analysis method developed by Bardin (2011). The analysis of the data shows us the contributions of the PRP in the initial training of the resident teachers through their insertion in the school environment and its training activities, the residents experienced in practice the direct contact with the routine of the school-field and the exercise of teaching, in two distinct situations, during and after a pandemic. Thus, the program proved to be fundamental during the initial training of future teachers, because through contact with the school environment, the student acquires knowledge and experiences that will be fundamental for the construction of the teaching identity and professional training.